2016
DOI: 10.1063/1.4944416
|View full text |Cite
|
Sign up to set email alerts
|

Including sheath effects in the interpretation of planar retarding potential analyzer’s low-energy ion data

Abstract: The interpretation of planar retarding potential analyzers (RPA) during ionospheric sounding rocket missions requires modeling the thick 3D plasma sheath. This paper overviews the theory of RPAs with an emphasis placed on the impact of the sheath on current-voltage (I-V) curves. It then describes the Petite Ion Probe (PIP) which has been designed to function in this difficult regime. The data analysis procedure for this instrument is discussed in detail. Data analysis begins by modeling the sheath with the Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The spacecraft potential is determined by a current balance model [Siddiqui et al, 2011] which uses the float potential and electron temperature as inputs. Both of these input quantities were well measured on MICA, and the resulting spacecraft potential is consistent with in situ thermal ion measurements by two different instruments Fisher et al, 2016]. Quantities arising from analysis include the…”
Section: Theorysupporting
confidence: 66%
“…The spacecraft potential is determined by a current balance model [Siddiqui et al, 2011] which uses the float potential and electron temperature as inputs. Both of these input quantities were well measured on MICA, and the resulting spacecraft potential is consistent with in situ thermal ion measurements by two different instruments Fisher et al, 2016]. Quantities arising from analysis include the…”
Section: Theorysupporting
confidence: 66%
“…In space, it was suggested that temperature estimates be obtained from the International Reference Ionosphere (IRI) model [5] or incoherent scatter radar measurements. The article also reports comparisons of inferred densities with those obtained from the IRI model, and independent measurements in a laboratory plasma [10]; both being deemed satisfactory, and constituting an improvement over estimates made with Jacobsen's original technique.…”
Section: Introductionmentioning
confidence: 87%
“…The main payload of ISINGLASS B included the energetic electron instrument Acute Precipitating Electron Spectrometer (APES) (Michell et al., 2016), the COrnell Wire BOom Yo‐yo System (COWBOYS) electric field instrument (Klatt et al., 2005), a retarding potential analyzer sensor Petite Ion Probe (PIP) (Fisher et al., 2016; Fraunberger et al., 2020), and a thermal electron plasma sensor Electron Retarding Potential Analyzer (ERPA) (Cohen et al., 2016; Frederick‐Frost et al., 2007). Multi‐point measurements were also made using PIPs carried by 4 sub‐payloads, known as BOBs (Roberts, Lynch, Clayton, Disbrow, et al., 2017, Roberts, Lynch, Clayton, Weiss, et al., 2017), ejected from the main payload.…”
Section: Overview Of Isinglass Bmentioning
confidence: 99%